Special papers Midterm results of sildenafil therapy in two complex patients with elevated pulmonary artery pressure after cavopulmonary connection - Białkowski, Jacek; Szkutnik, Małgorzata; Fiszer, Roland (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Two cases are presented. In the first patient (8-year-old boy) after Glenn operation without closure of pulmonary outflow from the common ventricle (SV-PA) despite transcatheter SV-PA closure increased mean pulmonary artery pressure (mPAP) (22 mm Hg) remained. After 6 months of sildenafil therapy he was catheterized again. His mPAP dropped to 10 mm Hg and a Fontan operation was subsequently performed. The second patient was a 25-year-old man, 20 years after a Fontan operation, presenting protein losing enteropathy and severe heart failure. All syndromes diminished significantly after medical therapy with sildenafil. Good clinical results of sildenafil therapy were maintained after 1 and 4 years of treatment. Chronic therapy with sildenafil can be beneficial in patients before and after the Fontan operation with elevated pulmonary artery pressure.